Laboratory analogues simulating Titan's atmospheric aerosols: Compared chemical compositions of grains and thin films. (1st September 2016) - Carrasco, Nathalie; Jomard, François; Vigneron, Jackie; Etcheberry, Arnaud; Cernogora, Guy
Abstract: Two sorts of solid organic samples can be produced in laboratory experiments simulating Titan's atmospheric reactivity: grains in the volume and thin films on the reactor walls. We expect that grains are more representative of Titan's atmospheric aerosols, but films are used to provide optical indices for radiative models of Titan's atmosphere. The aim of the present study is to address if these two sorts of analogues are chemically equivalent or not, when produced in the same N2 –CH4 plasma discharge. The chemical compositions of both these materials are measured by using elemental analysis, XPS analysis and Secondary Ion Mass Spectrometry. The main parameter probed is the CH4 /N2 ratio to explore various possible chemical regimes. We find that films are homogeneous but significantly less rich in nitrogen and hydrogen than grains produced in the same experimental conditions. This surprising difference in their chemical compositions could be explained by the efficient etching occurring on the films, which stay in the discharge during the whole plasma duration, whereas the grains are ejected after a few minutes. The higher nitrogen content in the grains possibly involves a higher optical absorption than the one measured on the films, with a possible impact on Titan's radiative models. Highlights: Chemical profiles of tholin films are provided by XPS and SIMS analysis. Films are homogeneous and O-free except a thin 20 nm external oxydized layer. Grains and films are produced simultaneously but their residence time is different. Films remain in the discharge and undergo continuous etching processes. This leads to a more graphitized material with lower H/C and N/C ratios.